GENETIC VARIABILITY AND CHARACTER ASSOCIATION IN MUNGBEAN (VIGNA RADIATA (L.) WILCZEK) - B Satheesh (African Journal of Environmental Economics and Management, 2024)
The present experiment was conducted to evaluate the mungbean genotype to assess the magnitude of genetic variability and to understand the heritable component of variation for seed yield and its component traits traits. The estimates of genotypic coefficient of variability, heritability and genetic advance were high for seed yield per plant, 100-seed weight, number of seeds per pod, number of pods per plant and number of nodes on main stem. The estimates of correlation revealed that seed yield had positive and significant correlation with number of pods per plant, 100-seed weight, days to first picking maturity, primary branches per plant and number of pods per cluster. Path coefficient analysis indicated that number of pods per plant, number of seeds per pod, number of clusters per plant had maximum direct contribution on seed yield.